Spatiotemporal evolution characteristics and influencing factors of digital industry in China - Hong Zhang; Fengjiao Li; Suqiong Wei; Lili Jiang; Junfeng Xiong; Tianwei Zhang (Scientific Reports)
Abstract In the era of the global knowledge economy, the rapid advancement of new-generation information technologies has positioned digital industry at the forefront of socio-economic development. Digital industrial clusters, comprising key enterprises and related institutions, have emerged as global hubs for technological innovation, drawing recognition from governments and international organizations. However, China’s digital industry faces challenges characterized by being “large but not strong” and experiencing “industrial structure softening.” This paper explores the temporal evolution and spatial distribution of China’s digital industry, shedding light on its unique patterns. This study reveals that China’s digital industry has progressed through four distinct phases, evolving from manufacturing-oriented to service-oriented, and experiencing dynamic stability. In terms of spatial distribution, it exhibits a pattern known as the “One Core, Three Poles, and Multiple Strongholds,” with Beijing as the core and Shanghai, Shenzhen, Hangzhou, among others, serving as growth poles. The study identifies factors influencing spatial distribution, including software development, patent authorizations, mobile phone penetration, industrial parks, digital finance, and foreign investment. Manufacturing-based digital industries prioritize innovation and IP protection, while service-based sectors rely on software development, innovation, and international collaboration. The GWR model demonstrates spatial variation, emphasizing the importance of tailored development strategies. This research contributes to understanding the dynamics of China’s digital industry and provides valuable insights for policymakers aiming to create an internationally competitive digital industry cluster.